THE INFLUENCE OF TEACHING CREATIVITY ON STUDENT LEARNING EFFECTIVENESS AT MTS - Solihin, Mohammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The teacher is a person who conveys the mandate of knowledge as well as educates and is responsible for the personal formation of students. The teacher is also a teacher, who is required to be a professional and creative teacher in teaching, therefore the teacher must have creativity to uphold professional values in his work as a teaching staff. The formulation of the problem in this research is